Universal health coverage in Pakistan: is the health system geared up to take on the challenge? - Babar Tasneem Shaikh; Nabeela Ali (BMC, 2023)
Abstract Background There is a strong and wide consensus that Pakistan must pursue universal health coverage (UHC) attainment as the driving force for achieving sustainable development goals by 2030. Nevertheless, several institutional and socioeconomic challenges may hinder the progress toward UHC. Main body It is important that the health system of Pakistan must be transformed to strengthen all three dimensions of UHC i.e. maximizing the population covered, increasing the range of services offered, and reducing the cost-sharing. To make UHC dream a reality in Pakistan, there are some pre-requisites to meet upfront: a) budgetary allocation for health as percentage of GDP must be increased; b) health system's readiness especially in the public sector ought to improve in terms of human resource and availability of essential services; c) safety nets for health must continue regardless of the change in the political regimes; d) decrease the reliance on donors' funding; and e) accountability to be ensured across the board for service providers, managers, administrators and policymakers in the health system. Conclusion COVID-19 pandemic has revealed some major gaps in the health system's capacity to deliver equitable healthcare, which is a cornerstone to achieving the UHC agenda. The priority-setting process will need to be aligned with the SDGs to ensure that the agenda for action towards 2030 is comprehensively addressed and successfully accomplished preferably before, but hopefully not beyond the targeted dates.